IMPLEMENTASI SISTEM PAKAR DALAM MENDIAGNOSA PENYAKIT PADA TANAMAN SAWI MENGGUNAKAN TEOREMA BAYES - Da Costa, Jeremias; Bulan, Semlinda Juszandri (Lembaga Pengembangan Kinerja Dosen, 2025)
Mustard is a major vegetable commodity in Kupang Tengah Subdistrict, Kupang Regency, which often suffers from disease attacks that can be detrimental to yields. Farmers' lack of knowledge about plant diseases and how to deal with them is a serious challenge in mustard cultivation. This research aims to implement an expert system to diagnose mustard plant diseases using Bayes' Theorem. The expert system is designed to mimic the expert's ability to diagnose diseases based on the symptoms displayed. Bayes' theorem was chosen because of its ability to analyze symptom data quickly and accurately. The results of this study can help farmers in diagnosing diseases, with a system error rate of 14%, and with a good category, this system can operate as expected.